European Digital Constitutionalism: Toward Norms of Free Journalism on Accountable Platforms - Bajčeta, Snežana (Political Life, 2025)
Digital platforms such as Facebook, TikTok, Instagram, and Microsoft are fundamentally transforming all spheres of social life, including journalism. In a platformized society, journalism is normatively destabilized due to the datafication, commodification, and moderation of journalistic content according to the criteria of the platform ecosystem (Van Dijck et al., 2018). To establish digital constitutional balance, the European Union, through a series of legislative acts, seeks to deplatformize the digital ecosystem within its borders and establish an institutional mechanism for upholding human rights and democratizing the digital sphere. Among these, the Digital Services Act serves as the central normative framework for governing digital platforms, aiming to shape the digital ecosystem based on the principle of accountability through a systemic approach and a comprehensive institutional arrangement. With the adoption of the European Media Freedom Act, journalism has taken on a special place in the current wave of regulation and, for the first time, has become the subject of a comprehensive intervention by the European Union. At the intersection of platform accountability and journalistic freedom, this paper explores the governance dynamics on and over platforms from the perspective of the normative challenge journalism faces in fulfilling its crucial informative role in the digital ecosystem.
Keywords: Digital Platforms; Digital Constitutionalism; Governance; Journalism; DSA; EMFA